Faktor-faktor yang berhubungan dengan kelengkapan pemberian imunisasi dasar lengkap pada balita usia 9-18 bulan - Gustina, Lisa; Wardani, Psiari Kusuma; Maesaroh, Siti (Wellness And Healthy Magazine, 2020)
Immunization is the process of introducing antibodies into the body. Giving immunizations to children should follow a predetermined schedule. But until now the problem of immunization still exists, many mothers who do not come to the posyandu provide immunization to their children. This is caused by various factors between her mother's work. Lack of mother's knowledge about immunization, the benefits of immunization, the dangers if the child is not immunized, and the side effects of vaccines that also cause fear of parents, are also one of the factors that influence the completeness of Complete Basic Immunization in children. The purpose of this study was to determine the factors related to the provision of complete basic immunization in infants aged 9-18 months in Wonosari Pringsewu year 2019. This type of quantitative research is an analytic research design with a cross-sectional approach. The population in this study were all toddlers aged 9-18 months in the Wonosari village of 78 toddlers. The sampling technique uses total sampling. Analysis of the data used using the chi-square test. The results of data analysis and processing found that there is a relationship between maternal employment status and complete basic immunization completeness obtained p-value 0.001 (less than 0.05) with an odds ratio of 7.295 (22,511-2,364), there is a relationship between maternal education, and complete basic immunization completeness obtained 0.0002 (less than 0.05) with an odds ratio of 5.588 (15.849-1.970) and there is a relationship between knowledge and completeness of complete basic immunization obtained P-value 0,001 (less than 0.05) with an odds ratio of 9.553 (31.895-2.861). It is hoped that the results of this study can be used as information to improve the understanding and insight of toddlers' parents about complete basic immunization, so parents can behave actively in providing basic immunizations.